Teaching English for special purposes aided by e-learning platform - Fučkan Držić, Biserka (Array, 2011)
In today’s fast moving world when students mention Internet more often than going to the library, colleges and universities have to adapt to Net Generation students who have grown up with information and communication technology and value experimental learning, working in teams and social networking. The paper presents the research performed with the students learning English for Special Purposes at the third semester of the study, at the Faculty of Geodesy, University of Zagreb. The main goal of the research was to find out whether combined teaching model can contribute to the language learning process through various activities. The tested sample consisted of two groups, each of 35 students, working on their assignments by face-to-face and online models. The findings of the research show whether ICT can contribute to enhance some segments of the language skills. The final test for all students analysed 6 elements of the written communication, 4 elements of the oral communication, communication quality with teacher and among students, average final grade and students’ attitudes towards new technology. The results have been analysed using SPSS (Statistical Package for Social Sciences). At the end suggestion for further implementation are given.